Gastric pH in patients premedicated with Esomeprazole or Famotidine undergoing routine surgery under general anaesthesia - Shrestha, BR; Shrestha, S; Moktan, S; Shrestha, OS (Journal of Kathmandu Medical College, 2013)
Background: Stress and anxiety in patients planned for surgery under anaesthesia may change pH of gastric secretion. Premedication of surgical patients with pH altering drugs may modify the pH favourably. With the advent of newer agents, premedication has been carried out with different agents. Most of the time choice of drug is made by the perioperative physician on his/her own. Objective: To study gastric pH in patients premedicated either with Esomeprazole or Famotidine. Methods: This is a randomized controlled double blind prospective study conducted in 150 patients of American Society of Anesthesiologists grade I and II posted for elective surgery under general anaesthesia. The patients enrolled in the study were randomly assigned to three groups having 50 patients in each. Group I (control group) did not receive any pH altering drug, Group II (Famotidine Group) received 40 mg of Famotidine and Group III (Esomeprazole Group) received 40 mg of Esomeprazole the night before surgery. The observer was totally blind about the groups or drugs given to the patients. On the day of surgery, after induction of anaesthesia gastric juice was obtained via nasogastric tube and was checked for pH using pH indicator paper. Results: The pH raised by Esomeprazole was statistically significant (p<0.001) when compared to that of control group or Famotidine group. The mean pH value in control group was less than 2.5 whereas the pH value was higher than 2.5 in patients premedicated with either Famotidine or Esomeprazole. Conclusions: Gastric pH is raised by Famotidine or Esomeprazole premedication prior to routine surgery, Esomeprazole being superior to Famotidine, p<0.001. Patients (84%) not premedicated with either of the drugs had pH less than 2.5. DOI: http://dx.doi.org/10.3126/jkmc.v1i2.8141 Journal of Kathmandu Medical College, Vol. 1, No. 2, Oct.-Dec., 2012: 71-76